OBSTACLES OF CHARTERED ACCOUNTANT FOR FULFILLMENT OBLIGATION ON CONTINUOUS LEARNING PROGRAM (CLP - Sugeng Riadi, Zahrah Indah Ferina (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2019)
This study discusses the obstacles faced by Chartered Accountants (CA) in fulfilling the obligations of credit learning (SKP) in continuing learning program (PPL) to maintain their professional competencies so as to be able to compete with accountants from other countries in the Asean Economic Community (AEC). This study used a descriptive qualitative approach with speakers from Indonesian Institute of Accountants (IAI) members who were registered CA in the Bengkulu Province. The results showed that most Chartered Accountants did not fulfill the SKP obligations due to the cost of training (cost), the time of the training conducted on weekdays (time) and training was rarely carried out in the area of ​​Bengkulu Province (location). The motivation of CA to maintain its competence is very good and ready to face the AEC which began in 2015